Perbedaan Self Efficacy dan Hasil Belajar Mahasiswa pada Mata Kuliah PKn Berdasarkan Gender di IAIN Takengon - Rahmahidayati Sari; Nurul Qomariah Ahmad (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This study aims to see the difference in self-efficacy and learning outcomes in the PKN course for Tadris Mathematics students based on gender at IAIN Takengon. Gender differences are one of the factors that affect differences self-efficacy and learning outcomes. This study uses a quantitative research method with a comparative type by comparing the self-efficacy and learning outcomes of female and male students. Sampling for this study used saturated sampling, namely taking all members of the population as a sample. This study uses inferential statistical analysis in processing the data by using the t-test with two independent samples because it compares 2 groups of independent samples that are not related. This research resulted in a conclusion that there was no difference in the self-efficacy of tadris mathematics students in PKN courses at IAIN Takengon based on gender. It was also concluded that there was no difference in the learning outcomes of PKN Tadris Mathematics students at IAIN Takengon based on gender.